Evaluation of maximum voided volume in Korean children by use of a 48‐h frequency volume chart - Kim, Sun‐Ouck; Kim, Kyung Do; Kim, Young Sig; Kim, Jun Mo; Moon, Du Geon; Park, Sungchan; Lee, Sang Don; Chung, Jae Min; Cho, Won Yeol (BJU international, 2012)
Study Type – Diagnostic (validating cohort) Level of Evidence 2a What's known on the subject? and What does the study add? The relationship between the maximum voided volume followed a linear curve. The formula presented, bladder capacity (mL) = 12 ×[age (years) + 11], is thought to be a reasonable one for Korean children. Korean children have a smaller bladder capacity than that reported in previous Western studies. OBJECTIVE • To develop practical guidelines for the prediction of normal bladder capacity in Korean children measured by a frequency volume chart (FVC), maximum voided volume (MVV) is an important factor in the diagnosis of children with abnormal voiding function. SUBJECTS AND METHODS • In all, 298 children, aged 3–13 years, with no history of voiding disorders volunteered for the study. The MVV was determined in 219 subjects by use of a completely recorded FVC. RESULTS • Linear regression analysis was used to define the exact relationship between age and bladder capacity. An approximate formula related age to bladder capacity as follows: bladder capacity (mL) = 12 ×[age (years) + 11]. CONCLUSIONS • The relationship between the MVV measured by a FVC by age (3–13 years) of Korean children followed a linear curve. • When applied to normal voiding patterns, the formula presented appears to be a reasonable one for Korean children.